2018
DOI: 10.1016/j.msea.2018.01.116
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic cyclic expansion extrusion (HCEE) as a novel severe plastic deformation process for producing long nanostructured metals

Abstract: In this paper, hydrostatic cyclic expansion extrusion (HCEE) is developed as a new severe plastic deformation technique for processing of the relatively longer ultrafine grained samples. Increasing the length of the processed sample, decreasing the processing load astonishingly, and increasing the hydrostatic stresses are the main advantages of HCEE. In This process lubricant surrounded around workplaces plays the main role in reducing the friction load and increase pressure hydrostatic. HCEE process was execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…It was shown that it can even process hard to deform materials. 78) Very recently, Samadpour et al 79) introduced an efficient technique in which the fluid pressure is used to remove frictional force and the material is deformed by hydraulic pressure. 80) This technique can be a promising step to design a frictionless process making possible the producing UFG large samples while applying relatively higher hydrostatic stresses.…”
Section: Hydrostatic Cyclic Expansion Extrusion (Hcee)mentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that it can even process hard to deform materials. 78) Very recently, Samadpour et al 79) introduced an efficient technique in which the fluid pressure is used to remove frictional force and the material is deformed by hydraulic pressure. 80) This technique can be a promising step to design a frictionless process making possible the producing UFG large samples while applying relatively higher hydrostatic stresses.…”
Section: Hydrostatic Cyclic Expansion Extrusion (Hcee)mentioning
confidence: 99%
“…A prominent example is related to HCEE process in which the friction force and deformation load are reduced to increase the sample size (l/d) from ³5 in regular CEE to more than 10 mm in HCEE. 80,140) In some of the semicontinuous processes in which drawing is applied at the outlet like ECAD, the tensile stress at the outlet side should not exceed from the yield strength of the material otherwise the plastic deformation is limited by yielding the sample. For example, the angle between input and output channels in ECAD process should be larger to prevent different damages in final products.…”
Section: Sizementioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The SPD processes provide for an accumulation of high-degree deformation, which contributes to the formation of high-angle grain boundaries. [4][5][6] UFG materials are characterized by an increased complexity of mechanical, physical and operational characteristics. [7][8][9][10] The main ones include properties such as tensile strength, yield strength under tension or compression, hardness, microhardness, corrosion resistance, and others.…”
Section: Introductionmentioning
confidence: 99%